2015
DOI: 10.1016/j.aej.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Emission and Performance analysis of hydrotreated refined sunflower oil as alternate fuel

Abstract: The experiments were conducted by using the hydrotreated refined sunflower oil as alternative fuel in a 4-stroke, stationary DI diesel engine at a constant speed of 1500 rpm. The effects of hydrotreated vegetable oil blends on diesel engine emission and performance were studied. The emission and performance were studied for different proportions such as HTSF B25 and HTSF B100 and at different loading conditions and comparison was made with petrodiesel. The emission and performance results of HTSF B25 and HTSF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Canola oil in diesel fuel showed significant reduction on CO emissions according to diesel fuel. Hemanandh and Narayanan conducted an experimental study with hydrotreated refined sunflower oil in a DI diesel engine at 1500 rpm constant engine speed. The usage of hydrotreated refined sunflower oil B25 and B100 reduced CO by 9%, 37%, HC by 42%, 55% NO x by 10% and 18.18% respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Canola oil in diesel fuel showed significant reduction on CO emissions according to diesel fuel. Hemanandh and Narayanan conducted an experimental study with hydrotreated refined sunflower oil in a DI diesel engine at 1500 rpm constant engine speed. The usage of hydrotreated refined sunflower oil B25 and B100 reduced CO by 9%, 37%, HC by 42%, 55% NO x by 10% and 18.18% respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, use of an alternate fuel is another way to reduce these pollutants. As experimentation, corn oil is blend with diesel and hydrogen is prepared in different ratios and tested in diesel engines for its performance and efficiency [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetable oils show most promising alternative fuel for Diesel engine due to their favourable properties very close to diesel fuel [1,2]. Earlier studies have reported significant engine results with different vegetable oils as fuels [3][4][5]. However, the use of edible oils directly affects the consumer in cost and availability when used as engine fuel.…”
Section: Introductionmentioning
confidence: 99%